Beneficial effects of pumpkin seed oil as a topical hair growth promoting agent in a mice model - Valiollah Hajhashemi; Parvin Rajabi; Mahdieh Mardani (Mashhad University of Medical Sciences, 2019)
Objective: Pumpkin (Cucurbita pepo L.) seed oil mainly consists of saturated and unsaturated fatty acids. Previously, it was reported that oral administration of pumpkin seed oil (PSO) improved hair growth in male pattern alopecia. This study aimed to evaluate hair promoting activity of topical PSO in an animal model. Materials and Methods: Male Swiss mice (25-30 g) were used. Dorsal hair of mice (2 x 2.5 cm) was gently removed. Groups were treated as follows: (A) Intact control (did not receive testosterone) (B) Testosterone solution only (5% w/v); (C) Testosterone (5%) + PSO (5%); (D) Testosterone (5%) + PSO (10%) (E) Testosterone (5%) + minoxidil (2%). Application of drugs (100 µl) was done for six days a week, for 3 weeks. Observational and microscopic examinations were performed and results of different groups were compared. Results: Topical application of testosterone significantly (p<0.01) prevented hair growth (compared with intact control). PSO (10%) increased hair growth score after 3 weeks and histopathological findings confirmed these results. After 3 weeks of treatment, the percentage of follicles in anagen phase was 95±4.6 and 44.4±15 for intact control and testosterone-onlytreated group, respectively. These percentages for PSO (10%) and minoxidil were 75±5.3 and 91.3±4.4, respectively and they could significantly (p<0.001) reverse the effects of testosterone. Conclusion: In conclusion, as topical application of PSO showed hair growth promotion, it might be regarded as a promising alternative for treatment of male pattern alopecia. Also, considering its composition, free fatty acids and minor components like phytoestrogens and vitamin E may have contributed to this effect.